Protocol for comparing gene-level selection on coding mutations between two groups of samples with Coselens - Jaime Iranzo; George Gruenhagen; Jorge Calle-Espinosa; Eugene V. Koonin (STAR Protocols, 2023)
Summary: The study of genes that evolve under conditional selection can shed light on the genomic underpinnings of adaptation, revealing epistasis and phenotypic plasticity. This protocol describes how to use the Coselens package to compare gene-level selection between two groups of samples. After installing Coselens and preparing the datasets, a typical run on a laptop takes less than 10 min. Coselens is best suited to analyze somatic mutations and data from experimental evolution, for which independently evolved samples are available.For complete details on the use and execution of this protocol, please refer to Iranzo et al. (2022).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.